IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PEMENUHAN HAK-HAK PENDIDIKAN PENYANDANG DISABILITAS DI KABUPATEN ENREKANG - Ahmad Mustanir; Muhammad Rais Rahmat Razak; Herman; Andi Asrifan (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2021)
This study aims to determine the implementation of government policies in Enrekang Regency, to find out the fulfillment of the rights of persons with disabilities and to find out how much the implementation of government policies towards the fulfillment of the rights of persons with disabilities in Enrekang Regency